MRI analysis of ACL tendon graft Intracanal Incorporation with polypropylene mesh implantation - Golovakha, Maxim; Shevelyov, Oleksiy; Bondarenko, Stanislav; Pertsov, Volodymyr (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2021)
Hamstring tendon graft remains one of the most popular for ACL reconstruction (ACLR). However, its disadvantage is long term ligamentation process and intracanal incorporation and delayed rehabilitation. One of the methods for stimulation of connective tissue growth is the implantation of polypropylene mesh (PPM), which are widely used in hernioplasty. Objective. To compare the MRI data dynamics of intracanal incorporation of tendon graft with implantation of PPM in bone canals. Methods. For evaluation of graft reconstruction in the femoral and tibial canals we used criteria based on the analysis of MRI images in PD FS and STIR sequences: the nature of the signal from the graft in the center of bone canal; general view of the graft; the nature of the MRI signal from the tissues around the graft on the tendons-bone border; the presence of synovial fluid in the canals and bone edema around them. Results of MRI of 75 patients who underwent «all-inside» ACLR with semitendinosus graft were analyzed. In the study group (40 patients) were compared to control group (35 patients) additionally implanted PPM around the ends of the tendon graft. Results. Intracanal graft incorporation in the group of patients with implantation of PPM occurred faster. The nature of the signal from the center of the bone canal and on the bone-tendon border progressed significantly faster in all observed terms. In the research group there was not presence of synovial fluid in the canals along the graft. Conclusions. Implantation of PPM around the ends of the ACL tendon autograft immersed in bone canals, leads, according to MRI data, to faster intra-canal incorporation. Key words. Knee joint, anterior cruciate ligament, arthroscopy.